Flexible Working Arrangement dan Work Life Balance pada Ibu yang Bekerja - Amilussholihati, Gina; Rahmi, Tuti (YASIN, 2025)
The increasing participation of women in the workforce presents challenges in balancing professional and domestic responsibilities, particularly for working mothers who face dual roles. This study aims to analyze the relationship between flexible working arrangements and work-life balance among working mothers in Payakumbuh City. A quantitative correlational approach was employed, involving 115 respondents selected through accidental sampling. The research instruments included a work-life balance scale adapted from Gunawan et al. (2019), based on Fisher et al. (2009), and a flexible working arrangement scale developed based on Hill et al. (2001). Data were analyzed using the Pearson product-moment correlation test with SPSS version 25. The results show that the majority of respondents fell within the moderate category for both variables, and a positive and significant relationship was found between flexible working arrangements and work-life balance, with a significance value of 0.038 and a Pearson correlation coefficient of 0.194. These findings indicate that the implementation of flexible work systems, such as flexplace and flextime, contributes to reducing dual-role conflict and enhancing the psychological well-being and productivity of working mothers. This study offers practical implications for institutions, particularly in the public sector, to develop work policies that support the achievement of optimal work-life balance.